2014
DOI: 10.1007/s00424-014-1543-x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Slc26a9 anion transporter alters intestinal electrolyte and HCO3 - transport and reduces survival in CFTR-deficient mice

Abstract: Slc26a9 is an anion transporter that is strongly expressed in the stomach and lung. Slc26a9 variants were recently found associated with a higher incidence of meconium ileus in cystic fibrosis (CF) infants, raising the question whether Slc26a9 is expressed in the intestine and what its functional role is. Slc26a9 messenger RNA (mRNA) was found highly expressed in the mucosae of the murine and human upper gastrointestinal tract, with an abrupt decrease in expression levels beyond the duodenum. Absence of SLC26a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 46 publications
(68 reference statements)
5
69
1
Order By: Relevance
“…First, recent studies in CFTR-deficient mice demonstrated that concomitant lack of SLC26A9 causes a significant increase in GI-related mortality suggesting that SLC26A9-mediated chloride secretion alleviates the severe meconium ileus-like intestinal obstruction in CF mice [81]. Second, studies in mice with experimental asthma demonstrated that similar to TMEM16A, SLC26A9 function was increased in Th2-mediated airway inflammation in parallel with goblet cell metaplasia and mucin hypersecretion [82,83].…”
Section: Slc26a9mentioning
confidence: 97%
“…First, recent studies in CFTR-deficient mice demonstrated that concomitant lack of SLC26A9 causes a significant increase in GI-related mortality suggesting that SLC26A9-mediated chloride secretion alleviates the severe meconium ileus-like intestinal obstruction in CF mice [81]. Second, studies in mice with experimental asthma demonstrated that similar to TMEM16A, SLC26A9 function was increased in Th2-mediated airway inflammation in parallel with goblet cell metaplasia and mucin hypersecretion [82,83].…”
Section: Slc26a9mentioning
confidence: 97%
“…It is conceivable that DRA does not participate in oxalate absorption in the proximal small intestine, even though it is prominently expressed there and responsible for 50–60% of baseline duodenal HCO 3 − secretion [2528]. In the Ussing chamber, the duodenum, unlike more distal segments, deteriorates rapidly with observable damage to the villi after 2 h followed by their near-complete destruction at 4 h [29].…”
Section: The Pathways and Mechanisms For Oxalate Transport Across Thementioning
confidence: 99%
“…This could not be explained by a transcriptional upregulation of DRA [16], but may be evidence of a direct functional coupling between DRA and PAT1 [38, 8991]. This is not surprising given that they are both apical Cl − /HCO 3 − exchangers with an overlapping distribution along the crypt–villus axis of the small intestine [25, 28, 30, 31, 80, 92]. In the absence of DRA, there was no corresponding increase in (PAT1-mediated) JsmOx by the distal ileum [17], suggesting PAT1 does not compensate in terms of oxalate secretion in the DRA-KO ileum.…”
Section: The Pathways and Mechanisms For Oxalate Transport Across Thementioning
confidence: 99%
“…Lohi et al report expression of SLC26A9 in the human pancreas 35 . Pancreatic expression was not reported in a study of adult human tissues 34 , although the importance of SLC26A9 function in the gastrointestinal tract of very young mice has been reported 36 . SLC26A9 encodes an anion transporter that can mediate chloride-bicarbonate exchange and sodium-coupled transport 37 .…”
Section: Discussionmentioning
confidence: 97%